Secondary battery and electronic device

By using surface-protected solid electrolyte materials and conductive lithium-philic layers in secondary batteries containing silicon negative electrodes, the problem of decreasing capacity retention rate caused by silicon pulverization and electrolyte consumption in the later stage is solved, and the cycle life and thermal safety performance of the battery are significantly improved.

CN120109315APending Publication Date: 2025-06-06NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510396782.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-06-06

AI Technical Summary

Technical Problem

The capacity retention rate of the secondary battery containing silicon negative electrodes decreased in the later stage due to silicon pulverization, electrolyte consumption and insufficient negative electrode kinetics, making the cycle life difficult to improve, and the thermal safety performance was insufficient.

Method used

The surface-protected solid electrolyte material is used to blend the silicon-containing negative electrode and coat it with a conductive lithium-philic layer, using an alloy and a hard carbon protective layer to reduce electrolyte consumption and improve kinetic performance.

Benefits of technology

Effectively alleviate the problem of silicon pulping, reduce electrolyte consumption, improve the fast charging performance, high-rate circulation performance and thermal safety performance of secondary batteries, and extend the cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120109315A_ABST
    Figure CN120109315A_ABST
Patent Text Reader

Abstract

The invention discloses a secondary battery and an electronic device, the secondary battery comprises a positive pole piece, a negative pole piece and an electrolyte, the negative pole piece comprises a negative pole material layer, and the negative pole material layer comprises a solid electrolyte; the solid electrolyte contains a lanthanum element, and the mass ratio of the lanthanum element is 0.042%-4% based on the mass of the negative electrode material layer; the ionic conductivity of the solid electrolyte is greater than or equal to 2 * 10 <-4 > S / cm; and the electronic conductivity of the solid electrolyte is less than or equal to 1 * 10 <-8 > S / cm. A coating layer is arranged on the surface of the solid electrolyte; the ionic conductivity of the coating layer is greater than or equal to 2 * 10 <-4 > S / cm; and the electronic conductivity of the coating layer is greater than or equal to 3 * 10 <-3 > S / cm. According to the secondary battery provided by the invention, the coated and modified solid electrolyte is mixed in the pole piece, so that the fast charging performance, the high-rate cycle performance and the thermal safety performance of the secondary battery are improved, and a reliable solution is provided for the practical application of a silicon-containing negative electrode battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of electrochemical technology, and specifically relates to a secondary battery and an electronic device. Background Art

[0002] At present, secondary batteries containing silicon negative electrodes face problems such as silicon powderization, electrolyte consumption and insufficient negative electrode dynamics, which lead to a significant decrease in capacity retention in the later stage and difficulty in improving cycle life. At the same time, the thermal safety performance of the battery is also insufficient, such as thermal runaway caused by electrolyte decomposition under high temperature conditions. These problems jointly restrict the practical application and performance optimization of secondary batteries containing silicon negative electrodes. Summary of the invention

[0003] In view of this, the present application provides a secondary battery and an electronic device, which, while having a high energy density, can effectively alleviate the silicon powdering problem, reduce electrolyte consumption, improve the negative electrode kinetics, enhance the fast charging performance, high-rate cycle performance and thermal safety performance of the secondary battery, and provide a reliable solution for the practical application of silicon-containing negative electrode batteries.

[0004] The inventor of the present application has found through research that in a secondary battery, a surface-protected solid electrolyte material is used to mix a silicon-containing negative electrode. Compared with a conventional lanthanum-containing solid electrolyte, the electrolyte is more stable to water and air and is not prone to lithium-hydrogen exchange reactions, thereby maintaining the high ion conductivity of the electrolyte, so that it plays an ion conduction role in the electrode, especially when the electrolyte of the silicon-containing negative electrode is exhausted in the late cycle, such an ion path is crucial to the battery capacity; it can achieve the retention of the electrolyte catalytic ability, and directional catalysis. The specific components in the electrolyte decompose to form an inorganic-rich SEI, effectively protecting the silicon-containing negative electrode to inhibit the consumption of electrolyte during the cycle and the resulting battery performance drop; in addition, it can also reduce the introduction of active protons into the battery due to the introduction of lanthanum-containing solid electrolytes, causing the deterioration of battery performance. It can effectively increase the performance improvement brought by the introduction of lanthanum-containing solid electrolytes into the battery. On this basis, the electrolyte material itself is no longer an electronic insulator after being coated with a conductive lithium-philic coating layer, which is conducive to reducing the negative impact of the mixed solid electrolyte on the electronic conductivity of the electrode. Moreover, the alloy and hard carbon protective layer used have high lithium ion conduction and diffusion capabilities after the negative electrode is embedded with lithium, and the presence of the protective layer will not affect the electrolyte's ability to conduct lithium. In addition, the lithium-philic coating layer can also induce uniform deposition of lithium metal during the later lithium deposition of the battery, reducing the risk of battery diving and short-circuit fire caused by lithium deposition. The ability to induce uniform lithium deposition also significantly improves the battery's cycling capacity at high rates. At the same time, the high ionic conductivity of the solid electrolyte and the conductive lithium-philic properties of the coating layer not only optimize the negative electrode kinetics, inhibit the decomposition of high-temperature electrolytes, and improve low-temperature power performance, but also the coating layer protects the electrolyte from air and moisture, retains the catalytic effect of lanthanum, promotes the formation of high-quality SEI film, reduces side reactions, and enhances the battery's storage performance and thermal safety. The design also supports uniform deposition of lithium metal, reduces the risk of lithium deposition, and improves high-rate cycling performance, providing a reliable solution for the practical application of high-energy-density silicon-containing negative-electrode batteries.

[0005] In a first aspect, the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode material layer comprises a negative electrode active material and a solid electrolyte;

[0006] The solid electrolyte contains lanthanum, and the mass of lanthanum accounts for 0.042% to 4% based on the mass of the negative electrode material layer;

[0007] The solid electrolyte has a coating layer on its surface, and the ionic conductivity of the coating layer is greater than or equal to 2×10 -4 S / cm; the electronic conductivity of the coating layer is greater than or equal to 3×10 -3 S / cm;

[0008] The ionic conductivity of the solid electrolyte is greater than or equal to 2×10 -4 S / cm;

[0009] The electronic conductivity of the solid electrolyte is less than or equal to 1×10 -8 S / cm. The present application adopts a lanthanum-containing solid electrolyte and a surface-coated conductive lithium-philic layer design. On the one hand, the coating layer protects the electrolyte from the influence of air and moisture, retains the catalytic effect of the lanthanum element, promotes the formation of a high-quality SEI film, and reduces side reactions; on the other hand, the conductive lithium-philic coating layer can induce the uniform deposition of lithium metal inside the negative electrode plate, significantly improving the fast charging performance and high-rate cycle performance of the secondary battery. In addition, the negative electrode plate of the present application can also support the design of a small CB battery, that is, the lithium insertion capacity per unit area of ​​the negative electrode plate can be smaller than that of the positive electrode, that is, the coating weight of the negative electrode can be greatly reduced, thereby improving the battery energy density. Specifically: when the lithium ions from the positive electrode are fully embedded in the negative electrode material, the excess lithium ions of the positive electrode are uniformly deposited inside the negative electrode in the form of lithium metal. When the solid electrolyte provided by the present application is not added, the lithium precipitation problem common in ion batteries is that the deposited lithium metal is deposited on the upper surface of the pole piece in the form of moss, filament or dendrite with high specific surface area, which not only leads to a sharp deterioration of the thermal safety performance of the battery, but also the lithium metal deposited on the surface is prone to form dead lithium due to electronic short circuit during the subsequent discharge process, causing the cycle capacity to decay rapidly. Therefore, the present application can achieve high safety performance and cycle performance in batteries with high energy density and small CB design.

[0010] In some embodiments, the coating layer is at least one of a lithium-philic alloy and a carbon material. By selecting the above-mentioned coating layer, the present application can effectively improve the electronic conductivity of the solid electrolyte, reduce its negative impact on the electronic conductivity of the electrode, and maintain its high ionic conductivity. The lithium-philic alloy and carbon material have excellent lithium ion conduction and diffusion capabilities after lithium insertion, ensuring that the coating layer does not hinder the lithium conductivity of the electrolyte. In addition, the lithium-philic coating layer can also induce uniform deposition of lithium metal during lithium precipitation in the later stage of the battery, reduce the risk of battery performance diving and short-circuit fire caused by lithium precipitation, and further improve the high-rate cycle performance and safety of the battery.

[0011] In some embodiments, the lithiophilic alloy includes at least one of the following metals: Mg, Zn, Ag, Au, B, Al, Si, Ga, Ge, In, Sn, Bi, Y, Pt.

[0012] In some embodiments, the thickness of the coating layer is 20nm to 100nm. The present application can ensure that the coating layer effectively protects the solid electrolyte while avoiding the influence of the conduction efficiency of lithium ions due to the excessive thickness of the coating layer by regulating the thickness of the coating layer within the above-mentioned appropriate range. The appropriate thickness range ensures that the coating layer has good electronic conductivity and lithium affinity, which can promote the uniform diffusion and deposition of lithium ions during the battery cycle, reduce the risk of lithium precipitation, and maintain the high ionic conductivity of the electrolyte. In addition, the thickness design also optimizes the interface contact between the coating layer and the electrolyte, further improves the cycle stability, high rate performance and thermal safety of the battery, and provides a reliable guarantee for the performance optimization of silicon-containing negative electrode secondary batteries.

[0013] In some embodiments, in the Raman spectrum of the carbon material, I D / I G The present invention relates to a method for preparing a carbon material having an I D / I G The value is regulated within the above range, which can effectively balance the graphitization degree and defect density of carbon materials, thereby optimizing their electronic conductivity and lithium ion diffusion performance. D / I G The value reflects the ratio of disordered structure (D peak) to graphitized structure (G peak) in carbon materials. Within this range, carbon materials have both good electronic conductivity and sufficient defect sites to promote the rapid insertion and extraction of lithium ions. This design not only enhances the conductivity and lithium affinity of the coating layer, but also improves the kinetic performance of the battery, enhances the cycle stability and high-rate performance, and further reduces the risk of lithium plating, providing a more reliable solution for the practical application of silicon-containing negative electrode secondary batteries.

[0014] In some embodiments, the thickness of the coating layer is 50nm to 200nm. The present application can ensure that the coating layer effectively protects the solid electrolyte while avoiding the obstruction of the lithium ion conduction efficiency due to the excessive thickness of the coating layer by regulating the thickness of the coating layer within the above-mentioned appropriate range. This suitable thickness range enables the carbon material to give full play to its high electronic conductivity and lithium affinity, promote the uniform diffusion and deposition of lithium ions, reduce the risk of lithium precipitation, and maintain the high ionic conductivity of the electrolyte. In addition, the thickness design optimizes the interface contact between the coating layer and the electrolyte, further improves the cycle stability, high rate performance and thermal safety of the battery, and provides a reliable guarantee for the performance optimization of silicon-containing negative electrode secondary batteries.

[0015] In some embodiments, based on the mass of the negative electrode plate, the mass proportion of the solid electrolyte is 0.1% to 8%, preferably 0.2% to 3%. The present application can ensure that the solid electrolyte effectively exerts its high ionic conductivity and catalytic effect while avoiding the mechanical properties and electronic conductivity of the negative electrode plate due to excessive addition by regulating the mass proportion of the solid electrolyte within the above-mentioned appropriate range. This ratio range ensures that the solid electrolyte can form a stable ion conduction network in the silicon-containing negative electrode, especially when the electrolyte is exhausted in the late cycle, the capacity of the battery can still be maintained. In addition, an appropriate amount of solid electrolyte helps to catalyze the decomposition of specific components in the electrolyte to form a high-quality SEI film, reduce electrolyte consumption, and inhibit side reactions, thereby improving the cycle life, storage performance and thermal safety of the battery. This design provides a more reliable performance optimization solution for the practical application of silicon-containing negative electrode secondary batteries.

[0016] In some embodiments, the particle sizes of the solid electrolyte are Dv90, Dv50 and Dv10 satisfying: 320nm≤Dv90≤1860nm, 93nm≤Dv10≤500nm, 2 / 5Dv90≤Dv50≤3 / 2Dv10. The present application can optimize the particle distribution of the solid electrolyte by regulating the particle sizes of Dv90, Dv50 and Dv10 within the above-mentioned appropriate range, ensuring that it forms a uniform and efficient ion conduction network in the negative electrode material layer. This particle size range is not only conducive to the full contact between the solid electrolyte and the negative electrode active material, improving the ion conduction efficiency, but also reducing the problem of local stress concentration or increased interface impedance caused by excessively large or small particles. At the same time, a reasonable particle size distribution helps to maintain the mechanical stability and electronic conductivity of the negative electrode sheet, and further improves the cycle performance, capacity retention rate and rate performance of the battery. This design provides a more reliable performance optimization solution for the practical application of silicon-containing negative electrode secondary batteries.

[0017] In some embodiments, the negative electrode active material includes at least one of a graphite material, a hard carbon material, a silicon element, a silicon-carbon material, a silicon-oxygen material, and modified materials thereof.

[0018] In some embodiments, the negative electrode active material is a silicon-carbon material, wherein the mass proportion of silicon element is 5% to 20% based on the mass of the negative electrode material layer. In the present application, based on the mass of the negative electrode material layer, the mass proportion of silicon element is regulated within the above-mentioned appropriate range, which can effectively alleviate the volume expansion problem of silicon during the charging and discharging process while making full use of the high specific capacity advantage of silicon material, and reduce silicon powderization and electrolyte consumption. This ratio range ensures that the negative electrode material layer has a high energy density and good structural stability, while maintaining the mechanical strength and electronic conductivity of the negative electrode sheet. In addition, an appropriate amount of silicon content helps to optimize the negative electrode kinetics, improve the cycle life and capacity retention rate of the battery, and reduce the risk of lithium plating. This design provides a more reliable performance balance solution for the practical application of silicon-containing negative electrode secondary batteries.

[0019] In some embodiments, after the secondary battery is cycled 300 to 350 times, the negative electrode plate is subjected to X-ray photoelectron spectroscopy analysis, and the test results at 80 nm from the surface of the negative electrode plate include peak A and peak B, the peak position of peak A is in the range of 184 eV to 186 eV, and the peak intensity is 1 A The peak position of peak B is in the range of 183eV to 180eV, and the peak intensity is 1 B au; satisfying 2.2≤I A / I B ≤7. The present application adjusts the peak intensity ratio of peak A to peak B within the above range, indicating that the SEI film formed on the surface of the negative electrode contains more LiPO x F y Compound. This SEI membrane component can effectively improve the stability and ionic conductivity of the SEI membrane, inhibit further decomposition of the electrolyte, and reduce the loss of active lithium, thereby improving the battery's cycle performance and capacity retention rate. At the same time, this ratio range also reflects the reasonable ratio of inorganic and organic matter in the SEI membrane, which helps to enhance the interface stability of the negative electrode sheet, reduce the interface impedance, and further improve the battery's rate performance and thermal safety. This design provides a more reliable performance optimization solution for the practical application of silicon-containing negative electrode secondary batteries.

[0020] In some embodiments, the electrolyte includes sulfite, and the mass proportion of sulfite is 0.5% to 3% based on the mass of the electrolyte. The present application can form a stable interface protection film (SEI film) in the electrolyte by regulating the content of sulfite within the above-mentioned appropriate range, effectively inhibiting the decomposition of the electrolyte and the occurrence of side reactions. The appropriate addition of sulfite helps to optimize the composition of the SEI film, and forms an organic SEI layer rich in organic sulfide outside the inner SEI rich in inorganic substances. The inner inorganic SEI is responsible for providing ionic conductivity and mechanical stability, while the outer organic component provides the flexibility of SEI, which can resist the rupture of the SEI film caused by the volume expansion of the silicon-containing negative electrode material during the cycle, thereby causing the fresh negative electrode to be exposed to the electrolyte and continue to react with the electrolyte. Thereby reducing the loss of active lithium and improving the cycle life and capacity retention rate of the battery. At the same time, this content range can also enhance the thermal stability of the electrolyte, reduce the risk of decomposition under high temperature conditions, and improve the thermal safety performance of the battery. In addition, the introduction of sulfite helps to improve the interface dynamics of the negative electrode plate, further improving the rate performance and low-temperature performance of the battery. This design provides a more reliable performance optimization solution for the practical application of silicon-containing negative electrode secondary batteries.

[0021] In some embodiments, the electrolyte further includes a first additive; the first additive includes at least one of vinylene carbonate and fluoroethylene carbonate; based on the mass of the electrolyte, the mass percentage of the first additive is 7% to 25%. The appropriate addition of vinylene carbonate (VC) and fluoroethylene carbonate (FEC) can optimize the composition of the SEI film, improve its ionic conductivity and mechanical stability, thereby reducing the loss of active lithium and significantly improving the cycle life and capacity retention of the battery. At the same time, this content range can also enhance the thermal stability and antioxidant capacity of the electrolyte, reduce the risk of decomposition under high temperature conditions, and improve the thermal safety performance of the battery.

[0022] In some embodiments, the electrolyte also includes lithium hexafluorophosphate, and the mass proportion of lithium hexafluorophosphate is 7% to 14% based on the mass of the electrolyte. The present application can provide sufficient lithium ion concentration in the electrolyte by regulating the mass proportion of lithium hexafluorophosphate within the above-mentioned appropriate range to ensure high ionic conductivity and good electrochemical performance of the battery. The appropriate addition of lithium hexafluorophosphate helps to form a stable SEI film on the surface of the negative electrode, inhibits the decomposition of the electrolyte and the occurrence of side reactions, thereby reducing the loss of active lithium and improving the cycle life and capacity retention rate of the battery. At the same time, this content range can also optimize the thermal stability and electrochemical window of the electrolyte, reduce the risk of decomposition under high temperature conditions, and improve the thermal safety performance of the battery. In addition, the introduction of lithium hexafluorophosphate helps to improve the rate performance and low temperature performance of the battery, and provides a more reliable performance optimization solution for the practical application of silicon-containing negative electrode secondary batteries.

[0023] In a second aspect, the present application provides an electronic device, comprising the secondary battery provided in the first aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A P1s spectrum of the SEI surface XPS characterization of the anode surface after cycling provided in a specific embodiment of the present application;

[0025] Figure 2 This is the F1s spectrum of XPS characterization of the anode SEI film surface after cycling;

[0026] Figure 3 The atomic ratio obtained from the XPS spectrum of the anode SEI film surface after cycling;

[0027] Figure 4 5C cycling performance of full cells with solid electrolyte blended and Si anode. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0029] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the implementation or examples are included in at least one implementation or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same implementation or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more implementations or examples in a suitable manner.

[0030] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0031] In this application, unless otherwise specified, the contents are measured by mass.

[0032] At present, secondary batteries containing silicon negative electrodes face problems such as silicon powderization, electrolyte consumption, and lithium precipitation caused by insufficient negative electrode dynamics, which leads to a significant decrease in capacity retention in the later stage and difficulty in improving cycle life. At the same time, the storage performance and thermal safety performance of the battery are also insufficient. The electrolyte is easy to decompose under high temperature conditions, and the power performance of the battery is poor under low temperature conditions. These problems jointly restrict the practical application and performance optimization of secondary batteries containing silicon negative electrodes.

[0033] In view of this, the present application provides a secondary battery and an electronic device, which, while having a high energy density, can effectively alleviate the silicon powdering problem, reduce electrolyte consumption, improve the negative electrode kinetics, enhance the fast charging performance, high-rate cycle performance and thermal safety performance of the secondary battery, and provide a reliable solution for the practical application of silicon-containing negative electrode batteries.

[0034] The inventor of the present application has found through research that in a secondary battery, a surface-protected solid electrolyte material is used to mix a silicon-containing negative electrode. Compared with a conventional lanthanum-containing solid electrolyte, the electrolyte is more stable to water and air and is not prone to lithium-hydrogen exchange reactions, thereby maintaining the high ion conductivity of the electrolyte, so that it plays an ion conduction role in the electrode, especially when the electrolyte of the silicon-containing negative electrode is exhausted in the late cycle, such an ion path is crucial to the battery capacity; it can achieve the retention of the electrolyte catalytic ability, and directional catalysis. The specific components in the electrolyte decompose to form an inorganic-rich SEI, effectively protecting the silicon-containing negative electrode to inhibit the consumption of electrolyte during the cycle and the resulting battery performance drop; in addition, it can also reduce the introduction of active protons into the battery due to the introduction of lanthanum-containing solid electrolytes, causing the deterioration of battery performance. It can effectively increase the performance improvement brought by the introduction of lanthanum-containing solid electrolytes into the battery. On this basis, the electrolyte material itself is no longer an electronic insulator after being coated with a conductive lithium-philic coating layer, which is conducive to reducing the negative impact of the mixed solid electrolyte on the electronic conductivity of the electrode. Moreover, the alloy and hard carbon protective layer used have high lithium ion conduction and diffusion capabilities after the negative electrode is embedded with lithium, and the presence of the protective layer will not affect the electrolyte's ability to conduct lithium. In addition, the lithium-philic coating layer can also induce uniform deposition of lithium metal during the later lithium deposition of the battery, reducing the risk of battery diving and short-circuit fire caused by lithium deposition. The ability to induce uniform lithium deposition also significantly improves the battery's cycling capacity at high rates. At the same time, the high ionic conductivity of the solid electrolyte and the conductive lithium-philic properties of the coating layer not only optimize the negative electrode kinetics, inhibit the decomposition of high-temperature electrolytes, and improve low-temperature power performance, but also the coating layer protects the electrolyte from air and moisture, retains the catalytic effect of lanthanum, promotes the formation of high-quality SEI film, reduces side reactions, and enhances the battery's storage performance and thermal safety. The design also supports uniform deposition of lithium metal, reduces the risk of lithium deposition, and improves high-rate cycling performance, providing a reliable solution for the practical application of high-energy-density silicon-containing negative-electrode batteries.

[0035] According to a first aspect of the present application, the present application provides a secondary battery, which includes a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode material layer includes a negative electrode active material and a solid electrolyte;

[0036] The secondary battery may be a common battery in the art that can be used continuously by activating the active material by charging after the battery is discharged; in some embodiments, the secondary battery includes but is not limited to a lithium-ion battery.

[0037] In the present application, the electrolyte comprises a base solvent and an additive. The negative electrode comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The positive electrode comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector.

[0038] This application mainly aims at making special improvements and limitations on the formula content of the solid electrolyte and the negative electrode active material (silicon carbon) of the negative electrode to obtain a secondary battery with stable performance.

[0039] <Negative electrode>

[0040] Specifically, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, and the negative electrode material layer includes a negative electrode active material and a solid electrolyte;

[0041] The solid electrolyte contains lanthanum, and the mass of lanthanum accounts for 0.042% to 4% based on the mass of the negative electrode material layer;

[0042] The solid electrolyte has a coating layer on its surface, and the ionic conductivity of the coating layer is greater than or equal to 2×10 -4 S / cm; the electronic conductivity of the coating layer is greater than or equal to 3×10 -3 S / cm;

[0043] The ionic conductivity of the solid electrolyte is greater than or equal to 2×10 -4 S / cm;

[0044] The electronic conductivity of the solid electrolyte is less than or equal to 1×10 -8 S / cm. As an example, the ionic conductivity of the coating layer can be 2×10 -4 S / cm, 3×10 -4 S / cm, 4×10 -4 S / cm, 5×10 -4 S / cm or the like or a value within the range of any two of these values. As an example, the electronic conductivity of the coating layer may be 3×10 -3 S / cm, 1×10 3S / cm or a value within the range of any two of these values. As an example, the ionic conductivity of the solid electrolyte may be 2×10 -4 S / cm, 4×10 -4 S / cm, 6×10 -4 S / cm, 8×10 -4 S / cm, etc. or values ​​within the range of any two of these values. The present application adopts a lanthanum-containing solid electrolyte and a surface-coated conductive lithium-philic layer design. On the one hand, the coating layer protects the electrolyte from the influence of air and moisture, retains the catalytic effect of the lanthanum element, promotes the formation of a high-quality SEI film, and reduces side reactions; on the other hand, the conductive lithium-philic coating layer can induce the uniform deposition of lithium metal inside the negative electrode plate, significantly improving the fast charging performance and high-rate cycle performance of the secondary battery. In addition, the negative electrode plate of the present application can also support the design of a small CB battery, that is, the lithium insertion capacity per unit area of ​​the negative electrode plate can be smaller than that of the positive electrode, that is, the coating weight of the negative electrode can be greatly reduced, thereby improving the battery energy density. Specifically: when the lithium ions from the positive electrode are fully embedded in the negative electrode material, the excess lithium ions of the positive electrode are uniformly deposited inside the negative electrode in the form of lithium metal. When the solid electrolyte provided by the present application is not added, the lithium precipitation problem common in ion batteries is that the deposited lithium metal is deposited on the upper surface of the pole piece in the form of moss, filament or dendrite with high specific surface area, which not only leads to a sharp deterioration of the thermal safety performance of the battery, but also the lithium metal deposited on the surface is prone to form dead lithium due to electronic short circuit during the subsequent discharge process, causing the cycle capacity to decay rapidly. Therefore, the present application can achieve high safety performance and cycle performance in batteries with high energy density and small CB design.

[0045] In some embodiments, the coating layer is at least one of a lithium-philic alloy and a carbon material. By selecting the above-mentioned coating layer, the present application can effectively improve the electronic conductivity of the solid electrolyte, reduce its negative impact on the electronic conductivity of the electrode, and maintain its high ionic conductivity. The lithium-philic alloy and carbon material have excellent lithium ion conduction and diffusion capabilities after lithium insertion, ensuring that the coating layer does not hinder the lithium conductivity of the electrolyte. In addition, the lithium-philic coating layer can also induce uniform deposition of lithium metal during lithium precipitation in the later stage of the battery, reduce the risk of battery performance diving and short-circuit fire caused by lithium precipitation, and further improve the high-rate cycle performance and safety of the battery.

[0046] In some embodiments, the lithiophilic alloy includes one of the following metals: Mg, Zn, Ag, Au, B, Al, Si, Ga, Ge, In, Sn, Bi, Y, Pt.

[0047] In some embodiments, the thickness of the coating layer is 20nm to 100nm. As an example, the thickness of the coating layer can be 20nm, 40nm, 60nm, 80nm, 90nm, 100nm, etc. or a value within the range of any two of these values. The present application regulates the thickness of the coating layer within the above-mentioned appropriate range, while ensuring that the coating layer effectively protects the solid electrolyte, it can avoid affecting the conduction efficiency of lithium ions due to the excessive thickness of the coating layer. The appropriate thickness range ensures that the coating layer has good electronic conductivity and lithium affinity, can promote the uniform diffusion and deposition of lithium ions during the battery cycle, reduce the risk of lithium precipitation, and maintain the high ionic conductivity of the electrolyte. In addition, the thickness design also optimizes the interface contact between the coating layer and the electrolyte, further improves the cycle stability, high rate performance and thermal safety of the battery, and provides a reliable guarantee for the performance optimization of silicon-containing negative electrode secondary batteries.

[0048] In some embodiments, in the Raman spectrum of the carbon material, I D / I G As an example, in the Raman spectrum of carbon materials, I D / I G It can be 0.8, 1.0, 1.2, 1.3, 1.5, 1.6, 1.7, 1.8, etc. or a value within the range of any two of these values. D / I G The value is regulated within the above range, which can effectively balance the graphitization degree and defect density of carbon materials, thereby optimizing their electronic conductivity and lithium ion diffusion performance. D / I G The value reflects the ratio of disordered structure (D peak) to graphitized structure (G peak) in carbon materials. Within this range, carbon materials have both good electronic conductivity and sufficient defect sites to promote the rapid insertion and extraction of lithium ions. This design not only enhances the conductivity and lithium affinity of the coating layer, but also improves the kinetic performance of the battery, enhances the cycle stability and high-rate performance, and further reduces the risk of lithium plating, providing a more reliable solution for the practical application of silicon-containing negative electrode secondary batteries.

[0049] In some embodiments, the thickness of the coating layer is 50nm to 200nm. As an example, the thickness of the coating layer can be 50nm, 80nm, 100nm, 120nm, 140nm, 180nm, 200nm, etc. or a value within the range of any two of these values. The present application can ensure that the coating layer effectively protects the solid electrolyte while avoiding the obstruction of the lithium ion conduction efficiency due to the excessive thickness of the coating layer by regulating the thickness of the carbon material within the above-mentioned appropriate range. This suitable thickness range enables the carbon material to give full play to its high electronic conductivity and lithium affinity, promote the uniform diffusion and deposition of lithium ions, reduce the risk of lithium precipitation, and maintain the high ionic conductivity of the electrolyte. In addition, the thickness design optimizes the interface contact between the coating layer and the electrolyte, further improves the cycle stability, high rate performance and thermal safety of the battery, and provides a reliable guarantee for the performance optimization of silicon-containing negative electrode secondary batteries.

[0050] In some embodiments, based on the mass of the negative electrode sheet, the mass proportion of the solid electrolyte is 0.1% to 8%, preferably 0.2% to 3%. As an example, the mass proportion of the solid electrolyte is 0.1%, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8%, etc. or a value within the range of any two of these values. The present application can ensure that the solid electrolyte effectively exerts its high ionic conductivity and catalytic effect while avoiding the mechanical properties and electronic conductivity of the negative electrode sheet due to excessive addition by regulating the mass proportion of the solid electrolyte within the above-mentioned appropriate range. This ratio range ensures that the solid electrolyte can form a stable ion conduction network in the silicon-containing negative electrode, especially when the electrolyte is exhausted in the late cycle, the capacity of the battery can still be maintained. In addition, an appropriate amount of solid electrolyte helps to catalyze the decomposition of specific components in the electrolyte to form a high-quality SEI film, reduce electrolyte consumption, and inhibit side reactions, thereby improving the cycle life, storage performance and thermal safety of the battery. This design provides a more reliable performance optimization solution for the practical application of silicon-containing negative electrode secondary batteries.

[0051] In some embodiments, the particle size of the solid electrolyte is Dv90, Dv50 and Dv10 satisfying: 320nm≤Dv90≤1860nm, 93nm≤Dv10≤500nm, 2 / 5Dv90≤Dv50≤3 / 2Dv10. As an example, the value of Dv90 can be 320nm, 500nm, 600nm, 800nm, 1000nm, 1200nm, 1300nm, 1500nm, 1700nm, 1800nm, 1860nm, etc. or a value in the range of any two of these values. As an example, the value of Dv10 can be 93nm, 110nm, 150nm, 200nm, 230nm, 250nm, 280nm, 300nm, 350nm, 400nm, 450nm, 480nm, 500nm, etc. or a value in the range of any two of these values. This application can optimize the particle distribution of the solid electrolyte by regulating the particle size of Dv90, Dv50 and Dv10 within the above-mentioned appropriate range, ensuring that it forms a uniform and efficient ion conduction network in the negative electrode material layer. This particle size range is not only conducive to the full contact between the solid electrolyte and the negative electrode active material, improving the ion conduction efficiency, but also reduces the problem of local stress concentration or increased interface impedance caused by excessively large or small particles. At the same time, a reasonable particle size distribution helps to maintain the mechanical stability and electronic conductivity of the negative electrode sheet, and further improves the battery's cycle performance, capacity retention rate and rate performance. This design provides a more reliable performance optimization solution for the practical application of silicon-containing negative electrode secondary batteries.

[0052] In some embodiments, the negative electrode active material includes at least one of a graphite material, a hard carbon material, a silicon element, a silicon-carbon material, a silicon-oxygen material, and modified materials thereof.

[0053] In some embodiments, the negative electrode active material is a silicon-carbon material, wherein the mass proportion of silicon element is 5% to 20% based on the mass of the negative electrode material layer. As an example, based on the mass of the negative electrode material layer, the mass proportion of silicon element can be 5%, 8%, 10%, 12%, 15%, 18%, 20%, etc. or a value within the range of any two of these values. In the present application, based on the mass of the negative electrode material layer, the mass proportion of silicon element is regulated within the above-mentioned appropriate range, which can effectively alleviate the volume expansion problem of silicon during charging and discharging while making full use of the high specific capacity advantage of silicon material, and reduce silicon powderization and electrolyte consumption. This ratio range ensures that the negative electrode material layer has a high energy density and good structural stability, while maintaining the mechanical strength and electronic conductivity of the negative electrode sheet. In addition, the appropriate amount of silicon content helps to optimize the negative electrode kinetics, improve the cycle life and capacity retention rate of the battery, and reduce the risk of lithium plating. This design provides a more reliable performance balance solution for the practical application of silicon-containing negative electrode secondary batteries.

[0054] In some embodiments, after the secondary battery is cycled 300 to 350 times, the negative electrode plate is subjected to X-ray photoelectron spectroscopy analysis, and the test results at 80 nm from the surface of the negative electrode plate include peak A and peak B, the peak position of peak A is in the range of 184 eV to 186 eV, and the peak intensity is 1 A The peak position of peak B is in the range of 183eV to 180eV, and the peak intensity is 1 B au; satisfying 2.2≤I A / I B ≤7. As an example, the value of IA / IB can be 2.2, 3.3, 4, 5.5, 6, 6.5, 7, etc. or a value within the range of any two of these values. The present application adjusts the peak intensity ratio of peak A to peak B within the above range, indicating that the SEI film formed on the surface of the negative electrode sheet contains more LiPO x F y Compound. This SEI membrane component can effectively improve the stability and ionic conductivity of the SEI membrane, inhibit further decomposition of the electrolyte, and reduce the loss of active lithium, thereby improving the battery's cycle performance and capacity retention rate. At the same time, this ratio range also reflects the reasonable ratio of inorganic and organic matter in the SEI membrane, which helps to enhance the interface stability of the negative electrode sheet, reduce the interface impedance, and further improve the battery's rate performance and thermal safety. This design provides a more reliable performance optimization solution for the practical application of silicon-containing negative electrode secondary batteries.

[0055] The negative electrode material layer also includes a negative electrode binder. The negative electrode binder can improve the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. The present application does not particularly limit the type of negative electrode binder, as long as it is a material that is stable to the solvent used in the manufacture of the electrolyte or electrode. In some embodiments, the negative electrode binder includes a resin binder. Examples of resin binders include, but are not limited to, fluororesins, polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, and the like. When an aqueous solvent is used to prepare the negative electrode mixture slurry, the negative electrode binder includes, but is not limited to, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or its salt, polyvinyl alcohol, and the like.

[0056] The negative electrode material layer also includes a conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent can be at least one of acetylene black, Ketjen black, carbon nanotubes, carbon fibers, carbon dots or graphene, and the above-mentioned carbon nanotubes can include but are not limited to at least one of single-walled carbon nanotubes or multi-walled carbon nanotubes.

[0057] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a polymer substrate covered with a conductive metal, etc. Among them, the conductive metal includes but is not limited to copper, nickel or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate or poly(p-phenylene terephthalamide). In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4μm to 12μm, and the thickness of the single-sided negative electrode material layer is 30μm to 160μm. In the present application, the negative electrode mixture layer can be arranged on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector or a partial area of ​​the negative electrode current collector. This application has no special restrictions as long as the purpose of this application can be achieved.

[0058] The present application has no particular restrictions on the compaction density of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the compaction density of the negative electrode sheet can be 1.0 g / cm 3 Up to 1.85g / cm 3 The present application has no particular limitation on the cold pressing load of the negative electrode plate, as long as the purpose of the present application can be achieved. For example, the cold pressing load of the negative electrode plate can be 3 tons to 30 tons.

[0059] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above conductive agent and the above binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the thickness of the conductive layer, as long as the purpose of the present application can be achieved, for example, the thickness of the conductive layer is 1μm to 10μm.

[0060] <Electrolyte>

[0061] In some embodiments, the electrolyte includes a sulfite, and the mass proportion of the sulfite is 0.5% to 3% based on the mass of the electrolyte. As an example, based on the mass of the electrolyte, the mass proportion of the sulfite can be 0.5%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.3%, 2.5%, 2.7%, 2.9%, 3%, etc. or a value within the range of any two of these values. The present application can form a stable interfacial protective film (SEI film) in the electrolyte by regulating the content of the sulfite within the above-mentioned suitable range, thereby effectively inhibiting the decomposition of the electrolyte and the occurrence of side reactions. The proper addition of sulfite helps to optimize the composition of the SEI film, forming an organic SEI layer rich in organic sulfide outside the inner SEI rich in inorganic substances. The inner inorganic SEI is responsible for providing ionic conductivity and mechanical stability, while the outer organic component provides the flexibility of SEI, which can resist the rupture of the SEI film caused by the volume expansion of the silicon-containing negative electrode material during the cycle, which in turn causes the fresh negative electrode to be exposed to the electrolyte and continue to react with the electrolyte. Thereby reducing the loss of active lithium and improving the cycle life and capacity retention of the battery. At the same time, this content range can also enhance the thermal stability of the electrolyte, reduce the risk of decomposition under high temperature conditions, and improve the thermal safety performance of the battery. In addition, the introduction of sulfite helps to improve the interfacial kinetics of the negative electrode sheet, further improving the rate performance and low temperature performance of the battery. This design provides a more reliable performance optimization solution for the practical application of silicon-containing negative electrode secondary batteries.

[0062] In some embodiments, the electrolyte further includes a first additive; the first additive includes at least one of vinylene carbonate and fluoroethylene carbonate; based on the mass of the electrolyte, the mass proportion of the first additive is 7% to 25%. As an example, based on the mass of the electrolyte, the mass proportion of the first additive is 7%, 8%, 10%, 12%, 15%, 17%, 18%, 20%, 21%, 22%, 24%, 25%, etc. or a value within the range of any two of these values. The appropriate addition of vinylene carbonate (VC) and fluoroethylene carbonate (FEC) can optimize the composition of the SEI film, improve its ionic conductivity and mechanical stability, thereby reducing the loss of active lithium and significantly improving the cycle life and capacity retention of the battery. At the same time, this content range can also enhance the thermal stability and antioxidant capacity of the electrolyte, reduce the risk of decomposition under high temperature conditions, and improve the thermal safety performance of the battery.

[0063] In some embodiments, the electrolyte further includes lithium hexafluorophosphate, and the mass proportion of lithium hexafluorophosphate is 7% to 14% based on the mass of the electrolyte. As an example, based on the mass of the electrolyte, the mass proportion of lithium hexafluorophosphate can be 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, etc. or a value within the range of any two of these values. The present application can provide sufficient lithium ion concentration in the electrolyte by regulating the mass proportion of lithium hexafluorophosphate within the above-mentioned appropriate range to ensure high ionic conductivity and good electrochemical performance of the battery. The appropriate addition of lithium hexafluorophosphate helps to form a stable SEI film on the surface of the negative electrode, inhibits the decomposition of the electrolyte and the occurrence of side reactions, thereby reducing the loss of active lithium and improving the cycle life and capacity retention rate of the battery. At the same time, this content range can also optimize the thermal stability and electrochemical window of the electrolyte, reduce the risk of decomposition under high temperature conditions, and improve the thermal safety performance of the battery. In addition, the introduction of lithium hexafluorophosphate helps to improve the rate performance and low temperature performance of the battery, and provides a more reliable performance optimization solution for the practical application of silicon-containing negative electrode secondary batteries.

[0064] <Positive electrode>

[0065] The present application has no particular restrictions on the positive electrode plate, as long as the purpose of the present application can be achieved. For example, the positive electrode plate includes a positive current collector and a positive electrode material layer arranged on at least one surface of the positive current collector. The present application has no particular restrictions on the positive current collector, as long as the purpose of the present application can be achieved. For example, the positive current collector may include a metal foil, such as an aluminum foil. In the present application, the positive electrode material layer includes a positive electrode active material. The present application has no particular restrictions on the type of positive electrode active material, and any positive electrode active material known in the art can be used, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium manganese oxide or lithium iron manganese phosphate.

[0066] The positive electrode material layer of the present application may also include a positive electrode conductor and a positive electrode binder. The present application has no particular restrictions on the positive electrode conductor and the positive electrode binder, as long as the purpose of the present application can be achieved. For example, the positive electrode conductor may include but is not limited to carbon materials, metals, etc. The carbon material may include at least one of conductive carbon black, carbon nanotubes, carbon fibers or graphene, etc. The metal may include metal powder or metal fiber. The positive electrode binder may include but is not limited to at least one of polyacrylic acid, polyacrylate, acrylate polymer, polyimide, polyvinyl alcohol, carboxymethyl cellulose or its salt or polyvinylidene fluoride.

[0067] <Isolation film>

[0068] In some embodiments, a separator is provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.

[0069] For example, in some embodiments, the isolation film includes a substrate layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure. The material of the substrate layer can be selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, the material of the substrate layer can be selected from polypropylene porous film, polyethylene porous film, polypropylene non-woven fabric, polyethylene non-woven fabric or polypropylene-polyethylene-polypropylene porous composite film.

[0070] A surface treatment layer is provided on at least one surface of the substrate layer. The surface treatment layer can be a polymer layer, an inorganic layer or a layer formed by a mixed polymer and an inorganic substance. Specifically, the inorganic layer includes inorganic particles and a binder. The inorganic particles can be selected from one or more combinations of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The binder can be selected from one or more combinations of polyvinylidene fluoride, a polymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.

[0071] According to a second aspect of the present application, the present application provides an electronic device, which includes the above-mentioned secondary battery.

[0072] The use of the secondary battery of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. For example, the electronic device includes, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc. In addition, the secondary battery of the present application is applicable to energy storage power stations, sea transport vehicles, and air transport vehicles in addition to the electronic devices listed above. Air transport vehicles include air transport vehicles within the atmosphere and air transport vehicles outside the atmosphere.

[0073] Test Method

[0074] (1) XPS test:

[0075] Sample preparation: The lithium-ion battery that has been cycled to a specified number of times was discharged to 3.0 V and disassembled to separate the negative electrode plate. The anode plate was rinsed 5 times with sufficient DMC and fully dried to obtain a clean sample.

[0076] Testing process: Ar plasma is used to etch the material surface, and the etching depth is controlled by adjusting the etching time and rate. The etched surface is tested for XPS to obtain XPS spectra at different depths from the surface. When testing XPS, the negative electrode material is tested using the ESCALAB Xi+ X-ray photoelectron spectrometer (XPS) of Thermo Scientific, and elements including B, C, F, La, Li, N, O, P, S, Si, and Ti are selected as analysis elements. The XPS total spectrum in the range of -8 to 1352 eV is tested at a scan rate of 20 eV / s, the XPS spectra of C 1s and O 1s are tested at a scan rate of 0.1 eV / s, and the XPS spectra of each element are tested at a scan rate of 0.067 eV / s to obtain the XPS test curve.

[0077] (2) Coating thickness test:

[0078] Sample preparation: The lithium-ion battery that has been cycled to a specified number of times is discharged to 3.0V and disassembled, and the negative electrode is separated. It is first cleaned with DMC and dried. The powder obtained by scraping the electrode is added to ethanol and ultrasonicated to obtain a uniformly dispersed suspension. The suspension is dropped on the TEM copper grid and sampled for testing.

[0079] TEM test coating thickness: Combine particle morphology and elements to determine the solid electrolyte, magnify the outer surface of the solid electrolyte, and observe the thickness of the amorphous layer on the surface of the solid electrolyte, which is the coating thickness.

[0080] (3) SEM test: The SEM characterization was recorded by a Philips XL-30 field emission scanning electron microscope at 10 kV, 10 mA. Silicon particles and graphite particles were distinguished and counted by backscattering mode (silicon particle areas are brighter and graphite particle areas are darker).

[0081] (4) Infrared test:

[0082] The lithium-ion battery that has been cycled to a specified number of times is discharged to 3.0V and disassembled to separate the negative electrode plate. Pre-test treatment is performed: a sample of length × width = 10mm × 10mm is cut, rinsed three times with DMC, and soaked in sufficient DMC for 2h before the plate is taken out and dried. The solid electrolyte material or the negative electrode plate after cycling is tested using an FTIR-1500 Fourier transform infrared spectrometer.

[0083] (5) Particle size test:

[0084] Add about 0.02 g of powder sample into a 50 ml clean beaker, add about 20 ml of deionized water, and then add a few drops of 1% surfactant to completely disperse the powder in the water. Ultrasonicate in a 120 W ultrasonic cleaner for 5 minutes, and use MasterSizer 2000 to test the particle size distribution.

[0085] (6) Ionic conductivity test:

[0086] Different solid electrolytes were prepared into high-density ceramic sheets (density 0.96) by cold pressing, and gold was sprayed on both ends of the ceramic sheets to make blocking electrodes. The prepared blocking electrodes were subjected to AC impedance testing with a frequency range of 1MHz to 10Hz and a disturbance amplitude of 10mV. The ionic conductivity σ of the solid electrolyte was calculated as follows: σ=d / Re×S.

[0087] Where d is the thickness of the sample under test (in cm); Re is the body impedance of the sample under test (in Ω), which can be obtained from the intersection of the semicircle arc and the oblique line in the Nyquist diagram of the electrochemical impedance spectroscopy; S is the effective area of ​​the electrode (in cm 2 ).

[0088] The ionic conductivity test results of different solid electrolyte materials were carried out three times, and the average value was obtained as follows: Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 The ionic conductivity is 2.12*10 -3 S / cm; Li 0.33 La 0.56 TiO 3 The ionic conductivity is 6.23*10 -3 S / cm; Li 7 La 3 Zr 2 O 12 The ionic conductivity is 8.15*10 -3 S / cm.

[0089] (7) Cycle test:

[0090] The test temperature is 25°C. The lithium-ion batteries of the embodiments and comparative examples are charged to 4.53V at 0.1C constant current, charged to 0.05C at constant voltage, and discharged to 2.8V at 0.1C constant current after standing for 5 minutes. The capacity obtained in the third cycle is taken as the initial capacity, and a cycle test is performed at 5C charge / 5C discharge. The capacity at each step is compared with the initial capacity to obtain a capacity decay curve.

[0091] The cycle performance is characterized by the number of cycles corresponding to a capacity retention rate of 70%, and a greater number of cycles indicates better cycle performance.

[0092] (8) Lithium salt consumption ratio test:

[0093] The lithium-ion battery that has been cycled to a specified number of times is discharged to 3.0V and disassembled. The separated pole pieces, diaphragms, and pocket bags are soaked in 50g of solvent DMC for more than 2 weeks, and are constantly stirred to fully dissolve the lithium salt in the battery. Then the DMC solution is tested for ion chromatography to obtain the remaining lithium salt concentration in the DMC solution. The amount of lithium salt dissolved in 50g DMC can be reversed, which is equal to the amount of lithium salt remaining in the battery. Then, it is compared with the theoretical amount of lithium salt in the liquid volume after the battery is formed, and the consumption ratio can be obtained.

[0094] (9) Hotbox window test: Place 5 fully charged batteries in a test furnace as a group, heat them up at a rate of 5°C / min, and keep them warm for 1 hour after reaching the set temperature. If none of the 5 batteries catch fire or explode, the test is considered passed. The highest temperature that the battery can pass is the Hotbox pass window.

[0095] Example 1-1

[0096] Secondary battery manufacturing

[0097] The solid electrolyte coating process is as follows:

[0098] (1) Pretreatment: First, the existing solid electrolyte LLZTO (Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 ) The nanoparticles are heated to 500 degrees at 5 degrees / min and calcined in air for more than 4 hours. Dry gas (dry air or dry nitrogen, etc.) is required when cooling. This pretreatment can reverse the side reactions that have occurred on the surface of La-containing solid electrolyte nanoparticles and restore the activity of the material.

[0099] (2) Alloy coating: The pretreated solid electrolyte is used as the substrate, and the lithium-philic alloy target to be sputtered is used as the emission source. The sputtering atmosphere is argon, the sputtering pressure is less than 5 Pa, the sputtering current is 100-200 mA, the sputtering voltage is 200 V, and the sputtering temperature is 200 ° C. Depending on the different target materials and alloy types, the sputtering time can be adjusted to 1 min-1 h.

[0100] Preparation of negative electrode: Preparation of silicon-carbon negative electrode sheet: The above-mentioned coated solid electrolyte is used as the modified solid electrolyte material, the mixed material of silicon and carbon (mass ratio of 50:50) is used as the negative electrode active material, Super P is used as the conductive agent, styrene-butadiene rubber is used as the binder, and sodium carboxymethyl cellulose (CMC, weight average molecular weight 90000) is used as the thickener. The modified solid electrolyte material, negative electrode active material, Super P, sodium carboxymethyl cellulose, and styrene-butadiene rubber are mixed in a weight ratio of 1:95:0.5:0.8:2.7, deionized water is added, and a negative electrode slurry is obtained under the action of a vacuum mixer, wherein the solid content of the negative electrode slurry is 45wt%; the active material layer slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 8μm, and dried at 80°C to form a negative electrode active material layer, and then cold pressed and cut to obtain a negative electrode sheet.

[0101] Preparation of positive electrode: LiCoO 2 , conductive agent acetylene black, binder polyvinylidene fluoride (PVDF, weight average molecular weight is 5×10 5 ) are mixed in a weight ratio of 94:3:3, added to N-methylpyrrolidone (NMP) solvent, and stirred evenly under the action of a vacuum stirrer to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 75wt%; the positive electrode slurry is evenly coated on the surface of the positive electrode current collector aluminum foil, and dried at 90°C to obtain a positive electrode sheet.

[0102] Preparation of the diaphragm: A polyethylene (PE) with a thickness of 8 μm and a porosity of 55% was selected as the base membrane, and a PVDF slurry and inorganic particles (flaky boehmite and Al2O3) were distributed and coated on at least one surface of the base membrane. 2 O 3 The mass ratio is 70:30) slurry, and drying is carried out to obtain a separator. The coating thickness on the surface of the separator is 3 μm.

[0103] Preparation of electrolyte: In an argon atmosphere glove box with a water content of less than 10ppm, dimethyl carbonate and diethyl carbonate (mass ratio 1:1) are mixed to obtain a basic solvent, and then ethylene carbonate, fluoroethylene carbonate, lithium hexafluorophosphate and other additives are added to the above-mentioned basic solvent, and the electrolyte is obtained after mixing evenly. Among them, based on the mass of the electrolyte, the mass proportion of lithium hexafluorophosphate is 12.5%, the mass proportion of ethylene carbonate is 10%, and the mass proportion of fluoroethylene carbonate is 10%.

[0104] Battery production: The above electrode is used as the negative electrode, and the PE porous polymer film is used as the separator. The positive electrode, separator, and negative electrode are stacked in order, so that the separator is placed between the cathode and the negative electrode to play a role of isolation, and then wound to obtain a bare cell. The bare cell is placed in an outer package, injected with the prepared electrolyte, and then packaged. After the formation, degassing, trimming and other process flows, a full battery is obtained.

[0105] The difference between Examples 1-2 to 1-27 and Comparative Examples 1 to 9 and Example 1-1 is that, except for adjusting the parameters according to Tables 1 to 2, the other conditions are consistent with Example 1-1. See Table 1 for the differences and Table 2 for the experimental test results. Among them, when carbon material coating is performed, the solid electrolyte coating process includes: (2) Hard carbon coating: The solid electrolyte obtained by pretreatment is spray-dried together with a 50% ethanol solution of phenolic resin at 80-150 degrees, and the phenolic resin is cross-linked to obtain a resin-coated solid electrolyte, which is recorded as a precursor. The precursor is then heated to 1000°C at 5°C / min under argon conditions and kept warm for 3-6 hours to obtain the target product.

[0106] Table 1

[0107]

[0108]

[0109]

[0110] Table 2

[0111]

[0112]

[0113] Result analysis: Combined with the experimental test data in Table 2, it can be seen that this application solves the problems of silicon powderization, electrolyte consumption and lithium precipitation of silicon-containing negative electrode secondary batteries by adopting lanthanum-containing solid electrolyte and surface coating design, and significantly improves the capacity retention rate and cycle life at high rates. The high ionic conductivity of the solid electrolyte and the conductive lithium affinity of the coating optimize the negative electrode kinetics, inhibit the decomposition of high-temperature electrolyte, and improve the thermal safety performance. The coating also protects the electrolyte from air and moisture, retains the catalytic effect of lanthanum, promotes the formation of high-quality SEI film, reduces side reactions, and enhances the thermal safety of the battery.

[0114] Table 3

[0115]

[0116] Result analysis: Combined with the experimental test results in Table 3, it can be seen that the optimization of the electrolyte formula further improves the cycle performance and thermal safety performance.

[0117] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the principles of the present application should be included in the protection scope of the present application.

Claims

1. A secondary battery, characterized in that: It includes a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode material layer includes a negative electrode active material and a solid electrolyte; The solid electrolyte contains lanthanum, and the mass proportion of the lanthanum is 0.042% to 4% based on the mass of the negative electrode material layer; The solid electrolyte has a coating layer on its surface, and the ionic conductivity of the coating layer is greater than or equal to 2×10 -4 S / cm; the electronic conductivity of the coating layer is greater than or equal to 3×10 -3 S / cm; The ionic conductivity of the solid electrolyte is greater than or equal to 2×10 -4 S / cm; The electronic conductivity of the solid electrolyte is less than or equal to 1×10 -8 S / cm.

2. The secondary battery according to claim 1, characterized in that: The coating layer is at least one of a lithium-philic alloy and a carbon material.

3. The secondary battery according to claim 2, characterized in that: The lithium-philic alloy includes one of the following metals: Mg, Zn, Ag, Au, B, Al, Si, Ga, Ge, In, Sn, Bi, Y, Pt.

4. The secondary battery according to claim 3, characterized in that: The coating layer has a thickness of 20 nm to 100 nm.

5. The secondary battery according to claim 2, characterized in that: In the Raman spectrum of the carbon material, I D / I G It is 0.8-1.

8.

6. The secondary battery according to claim 5, characterized in that: The coating layer has a thickness of 50 nm to 200 nm.

7. The secondary battery according to claim 1, characterized in that: Based on the mass of the negative electrode plate, the mass proportion of the solid electrolyte is 0.1% to 8%, preferably 0.2% to 3%.

8. The secondary battery according to claim 1, characterized in that: The particle sizes of the solid electrolyte Dv90, Dv50 and Dv10 satisfy: 320nm≤Dv90≤1860nm, 93nm≤Dv10≤500nm, 2 / 5Dv90≤Dv50≤3 / 2Dv10.

9. The secondary battery according to claim 1, characterized in that: The negative electrode active material includes at least one of graphite material, hard carbon material, silicon element, silicon-carbon material, silicon-oxygen material and modified materials thereof.

10. The secondary battery according to claim 9, characterized in that: The negative electrode active material is a silicon-carbon material, wherein the mass proportion of silicon element is 5% to 20% based on the mass of the negative electrode material layer.

11. The secondary battery according to claim 1, characterized in that: After the secondary battery is cycled for 300 to 350 cycles, the negative electrode plate is subjected to X-ray photoelectron spectroscopy analysis. The test result at 80 nm from the surface of the negative electrode plate includes peak A and peak B. The peak position of peak A is in the range of 184 eV to 186 eV, and the peak intensity is 1 A The peak position of the B peak is in the range of 183eV to 180eV, and the peak intensity is 1 B au; satisfying 2.2≤I A / I B ≤7.

12. The secondary battery according to claim 1, characterized in that: The electrolyte includes sulfite, and based on the mass of the electrolyte, the mass proportion of the sulfite is 0.5% to 3%.

13. The secondary battery according to claim 1, characterized in that: The electrolyte further includes a first additive; the first additive includes at least one of vinylene carbonate and fluoroethylene carbonate; Based on the mass of the electrolyte, the mass of the first additive accounts for 7% to 25%.

14. An electronic device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 13.